PENGARUH SENSORY EXPERIENCE DAN EMOTIONAL EXPERIENCE TERHADAP MINAT BELI ULANG TIKET BIOSKOP (Studi pada Konsumen Bioskop Platinum Cineplex MGM Kolaka) - Anas Tasya; Muhamad Stiadi; Hanif Kurniadi (Jurnal Ekonomi Bisnis Kompetif, 2026)
This study aims to analyze the influence of sensory experience and emotional experience on repurchase intention of cinema tickets at Platinum Cineplex MGM Kolaka. This research uses a quantitative approach with data collected through questionnaires distributed to 120 respondents. Data analysis was conducted using Structural Equation Modeling based on Partial Least Square (PLS). The results show that sensory experience has a positive and significant effect on repurchase intention. Emotional experience also has a positive and significant effect on repurchase intention. The R-square value of 0.601 indicates that sensory experience and emotional experience explain 60.1% of the variance in repurchase intention. These findings indicate that sensory and emotional experiences play an important role in increasing consumer repurchase intentions